2020
DOI: 10.1038/s41477-020-00814-9
|View full text |Cite
|
Sign up to set email alerts
|

Forest-linked livelihoods in a globalized world

Abstract: orests provide essential livelihoods and environmental services. They harbour a disproportionate amount of the world's biodiversity, regulate key aspects of the global carbon cycle and weather patterns, and contribute directly to national incomes and the local livelihoods of millions of people worldwide. Their role in sustainability transitions is re-emphasized by multiple current international sustainability agendas. Forests can be linked to most-if not all-of the Sustainable Development Goals through contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 58 publications
0
39
0
5
Order By: Relevance
“…., T i }, µ i,t 0, σ 2 µ It has to be noted that these long-run coefficients are superconsistent, i.e., the distribution of the estimated coefficients converges to the real value as the sample size tends to infinity [36]. However, their standard errors are large and unreliable, and thus not robust, so statistical inference is not straightforward [3,49]. Thus, we have only used those estimates for our sample without performing statistical inference (see Appendix C for futher explanation).…”
Section: Long-run Model Specifications (With and Without Agricultural...mentioning
confidence: 99%
See 3 more Smart Citations
“…., T i }, µ i,t 0, σ 2 µ It has to be noted that these long-run coefficients are superconsistent, i.e., the distribution of the estimated coefficients converges to the real value as the sample size tends to infinity [36]. However, their standard errors are large and unreliable, and thus not robust, so statistical inference is not straightforward [3,49]. Thus, we have only used those estimates for our sample without performing statistical inference (see Appendix C for futher explanation).…”
Section: Long-run Model Specifications (With and Without Agricultural...mentioning
confidence: 99%
“…The multiple implications of changes in forest cover for climate change and livelihoods have made deforestation a global problem of public concern [2]. As a result, several international sustainability agendas have emphasized the role of forest in transition to sustainability, with special attention to tropical and subtropical regions [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Agricultural expansion into natural areas has helped to meet the growing global demand for food, feed, and fiber (Godfray et al, 2010), but has also produced unsustainable land-use outcomes. This is particularly the case where agricultural frontiers expand into tropical and subtropical forests, triggering globally-relevant greenhouse gas emissions (Carlson et al, 2017), biodiversity losses (Chaplin-Kramer et al, 2015), and major livelihood impacts on forestdependent people (Andersson & Agrawal, 2011;Oldekop et al, 2020). Yet, much of the agricultural expansion during the past decades has taken place in the tropics (Gibbs et al, 2010), where most of the last uncultivated, productive lands are found (Lambin et al, 2013;Ramankutty et al, 2002).…”
Section: Introductionmentioning
confidence: 99%